2003
DOI: 10.1177/1096348003027002001
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Management Education Incorporating Written or Simulation Cases: An Empirical Test

Abstract: In the context of hospitality education, this article reports on an empirical study of student learning considering four factors: strategic management skills, team process skills, level of difficulty, and overall perceived learning. Results of the empirical study suggest that the use of management computer simulation cases facilitates greater educational development than does the use of written cases (or a combination) as perceived by hospitality students in a capstone strategic management course. Discussion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
14
1
Order By: Relevance
“…In the analysis of simulation in relation to hospitality industry, students benefit mosts in financial analysis and marketing in relation to strategic management process and strategic decision making (Kendal & Harrington, 2003). This study also indicates that students appreciate the multidisciplinary qualities of business simulation.…”
Section: Discussionmentioning
confidence: 67%
“…In the analysis of simulation in relation to hospitality industry, students benefit mosts in financial analysis and marketing in relation to strategic management process and strategic decision making (Kendal & Harrington, 2003). This study also indicates that students appreciate the multidisciplinary qualities of business simulation.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies focus on one teaching method, such as the case method (Jennings, 1996) and business simulation games (Keys, 1997;Knotts and Keys, 1997;Wolfe, 1997;Wolfe and Roge, 1997). With regard to teaching strategic management in tourism and hospitality schools in particular, a number of studies have been undertaken by Kendall and Harrington (2003), Martin and McEvoy (2003), Russell and Russell (1996). However, they mainly focus on business simulation games.…”
Section: Introductionmentioning
confidence: 98%
“…Following exposure to business simulations, students' performance outcomes have been measured by self-reporting, and by group and individual assessments (Adobor & Daneshfar, 2006;Gopinath & Sawyer, 1999;Washbush & Gosen, 1998). Both Tompson and Dass (2000) and Kendall and Harrington (2003) adopted control groups and, using case study simulations, the former showed that over time students' self-efficacy improved (Tompson & Dass, 2000) and, in turn, facilitated greater educational development (Kendall & Harrington, 2003). Furthermore, Bandura and Cervone (1986), p. 93 identified that self-efficacy affects and influences individual's motivations and goal setting behaviour.…”
Section: Influence Of Realism On Knowledge Enhancementmentioning
confidence: 98%
“…In the initial phase, RO subsumes comprehension of the decision-making process and the relationship between decision sets. Typically students put their thoughts and observations into writing through the preparation of a business plan and initial budget (Chen & Downing, 2006;Edelheim & Ueda, 2007;Kendall & Harrington, 2003;Marriott, 2004;Martin & McEvoy, 2003). RO leads directly to AC where an initial strategy is prepared within the parameters of the simulation based upon the business plan and budget (Chen & Downing, 2006).…”
Section: Hots Business Simulation Programmementioning
confidence: 99%
See 1 more Smart Citation